Analysis of the Concept of Sustainable Tourism in Maratua Island, Berau Regency, East Kalimantan Province - Luki Adiati Pratomo; Yandi Rama Krisna (Journal of Social Research, 2023)
Sustainable tourism based on marine tourism on maratua island, berau regency, east Kalimantan province, Indonesia has challenges and perspectives from the side of tourists and tourists. PT. X and PT. Y was chosen as the object of research because it has CHSE certification from the Indonesian Ministry of Tourism and Creative Economy. The implementation of sustainable tourism has challenges in the accessibility sector where the high price of airfares to berau districts. The ISO 26000 approach to the core subject environment is the basis for tourism actors to carry out the concept of sustainable tourism. The relevance to the SDGs for this research will focus on SDGs No. 8 on economic improvement and SDGs No. 14 on marine ecosystems. Tourists who have visited PT. X and PT. Y 97% stated that they would return to maratua to re-enjoy the beauty of maratua island. As many as 47% of tourists feel very satisfied with the services carried out by PT. X and PT. Y.